The Application of Flowcharts in Understanding Programming Logic for New Students - Veny Vita Ponggawa; Muhammad N. Annas; Timothy P.P Boediman; Ezra R. Abdullah; Villarreal J.F Ramopolii (Cerdika: Jurnal Ilmiah Indonesia, 2026)
Background: Flowcharts serve as visual tools that support logical thinking through tangible diagrammatic representation. By using simple and universal symbols, students can represent program flow and logical structures more clearly before translating them into actual code. This visual approach may be particularly beneficial for first-year students who struggle with the abstract nature of programming concepts. Objective: This study aims to determine the effectiveness of implementing flowcharts in improving programming logic comprehension among first-year students with no prior programming experience. Methods: This research employed a qualitative descriptive approach with observational case study design. Participants were first-year students enrolled in introductory programming courses at Politeknik Negeri Manado. Data were collected through structured observation of classroom sessions, document analysis of student-produced flowcharts and corresponding code, and descriptive narration of student thought processes. Thematic analysis was applied to identify patterns in student performance, common error types, and learning experiences. Results: The findings demonstrate that students who consistently use flowcharts show significant improvement in programming logic understanding compared to those who seldom use them. Flowcharts help students construct systematic problem-solving approaches, visualize logical relationships, identify gaps in reasoning before coding, and reduce logical error rates in written code. Students demonstrated improved comprehension of sequential execution, conditional branching, iteration, and input-output operations. Flowchart users also showed enhanced debugging capabilities, using diagrams as references to locate and correct logical errors efficiently.